Nilai Moral Tokoh Utama Dalam Film Mulan Karya Niki Caro (Kajian Sosiologi Sastra) - Kevina Winata; Yohan Yusuf Arifin (Jayapangus Press, 2023)
The film Mulan by Niki Caro tells the story of the struggle of a girl named Hua Mulan who disguises herself as a man to replace her sick father by joining the military service to protect the country from attacks by the Rouran Nation based on a decree issued by the Chinese empire. This study aims to get a description of how the moral values ​​contained in the main character Mulan are reflected in every action she takes. The method used in this research is descriptive qualitative because this research describes, explains and analyzes the data to answer each existing problem formulation. The data collection technique in this research was by watching the film Mulan, paying attention and recording every dialogue/sentence related to moral values. The writer then analyzes the research data based on the theory of moral values ​​which mentioned by Suseno (1987).The results of the study show that the character Mulan reflects moral values consisting of honesty, being yourself, being responsible, moral independence, moral courage, humility and criticality. As the main character, Mulan already reflects moral values that can be the basis and guide for human life in life.